Pengaruh Store Atmosphere dan Lokasi Usaha terhadap Keputusan Pembelian Konsumen - Nur Fadilah Ayu Sandira; Mustari; Agus Syam; M. Ihsan Said Ahmad; Muhammad Dinar (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
This study aims to determine the effect of store atmosphere and business location on the purchasing decisions of consumer at Pattaya Thaitea Drink, in the District of Rappocini City of Makassar. This study is quantitative descriptive. The population in this study were all pattaya thaitea drink consumers whose number could not be determined and a sample are 100 respondents who are consumers of pattaya thaitea drink. Data collection is done with observation, documentation, and questionnaires. The analysis technique used is multiple linear regressions. The result of this study show that store atmosphere and business location has positive significant effect on puchasing decision of consumer at pattaya thaitea drink both partially and simultaneously. In this study the most, dominant influential variable is store atmosphere variable because it has a higher regression coefficient value than value of business location regression.